The Characteristics of MSME Entrepreneurs in Surakarta, Indonesia - Riani, Asri Laksmi; Prabowo, Agung; Andriyani, Mega Shintya (Department of Management, Faculty of Economics and Business, Brawijaya University, 2019)
This study aims to characterize the profile of entrepreneurs from micro, small and medium enterprises (MSME) and core business employees in Surakarta, one of the heritage city in Indonesia. The characteristics examined in this study are the need for achievement, locus of control, tolerance for ambiguity, creativity/innovation, self-confidence, propensity to risk, and a sense of self-sufficiency/freedom. This study also attempts to determine the distinguishing characteristics between entrepreneurs and core business employees. Forty core business employees and thirty-six entrepreneurs were selected using purposive sampling method and questionnaires as the research instruments. Data testing was performed using descriptive statistical analysis methods and independent sample t-test to examine the differences in the characters reflected in the sample studied. The test results indicate that there are significant differences between entrepreneur and core business employees in their character, including the need for achievement, ambiguity tolerance, creativity/innovation, propensity to risk, and a sense of self-sufficiency/freedom. However, there is no significant difference in the character of self-confidence and locus of control. In addition, descriptive statistical tests show that entrepreneurs have a higher mean score on all aspects of the characteristics than core business employees.